ڕۆڵی دەسەڵاتدارانی مەغۆلی ئیلخانی لە پەرەپێدانی زانست لە هەرێمی ئازەربایجان (656-736ك / 1258-1335ز) (توێژینەوەی هەڵێنجراو) - الدین, عطا عبدالرحمن محی; حسن, چرا محمود (Sulaimani Journal for Humanities, 2023)
After their occupation, the Mongols were influenced by the civilization of the countries they conquered like the Chinese and the Islamic civilizations. They borrowed much of the occupied countries’ civilized phenomena from all the different fields of the economic, political, and social systems such as tradition, religion, arts, literature, science, and so on. Even some of their kings converted to Islam. Mongolian Elkhany kings were interested in science and information and they wanted to spread their interest in the regions under their control like Azerbijan. Hence, Holako established an astrological base in Muagha in the year (657H./ 1258A.D.) After this date the city took the leadership of the world scientific movement at that period. When Ghazan Khan built his dome (at Shanb or Sham) in Tabreez in the year (697H./ 1297A.D.), he has built many scientific institutes and bases there. Oljaito Muhammad Khudabanda did the same thing; when he built the city of Sultaniyah in the year (704H./ 1304A.D.), he built many scientific institutions like schools, mosques, Khanaqa, worshipping corners, Dar-el-Quraan, and Dar-el-Hadith, hospitals, and so on. In the same way the other Mongolian Elkhany took great interest in building schools and scientific institutes and providing them with the necessary supplies. Mongolian Elkhany kings’ palaces have become symposium centers of scientists, learned men, men of letters, poets, philosophers, astrologists, historians, and writers in which a lot of scientific, philosophical and critical debates were held. The role of the ministers in the scientific development in Azerbaijan Region and the other regions under their control was significant; it is worth of mentioning that most of those ministers were scientists or at least interested in science like Shamsaddin Muhammad el-Jweny, Aladdin Atta-el-Malik el-Jweny’, brother Rashid-ed-din Fadhl Allah el-Hamadany, Taj-ed-dinAli Shah, Gayath-ed-din Muhammad son of Rashid-ed-din Fadhl Allah el-Hamadany. They had a great role in building scientific institutions or they had done great efforts in these fields. Though the Islamic State was declining as a result of the Mongolian attacks and later occupation, a large number of the Islamic scientists and thinkers were killed, libraries and scientific center were destroyed, but in that period the scientific fields of astrology, philosophy, religious beliefs, history, medicine, chemistry, languages, literature and poetry were in the center of interest. Muslim scientists played a significant role in the progress and increase of the scientific researches and the Mongolian Elkhany kings motivated them in their work. Thus, as a result of interaction and borrowing, Mongolian Elkhany kings stepped to another stage of civilization and civilized development which had a direct impact on the regions under their control especially the Region of Azerbaijan and its emergence on the political, historical, and scientific stage.
Keywords: Mongolian Elkhany State; science; Azerbaijan